Per una teoria generale (disgiunta ma unificata) del metodo - Mario Gennari (Firenze University Press, 2015)
What is a general methodology of science? What is a general theory of method? The article examines the two questions and summarizes the passages that connect - not only in a separate but also in a unified way - recognition, understanding, reasoning and abduction. Then induction, deduction, explanation and interpretation, in order to come finally to the meaning of fact. The general theory of method not divides the natural sciences, but blend them in an unitary project.